أثر التیسیر في الفتاوى المعاصرة دراسة تأصیلیة تطبیقیة -الأحوال الشخصیة أنموذجا - منصور, لیلى (University of Eloued-جامعة الوادي, 2015)
In this age in which abounded chaos and holding it matters, colorful Fatwa curricula in it, pulling many researchers seriously in order to shed light on the general approach in advisory, they edited studies on these approaches to its importance, and came this study addressed them .aside of: the impact of easing in contemporary fatwas This study has tried to prove the existence of the project and the exact easing controls legitimacy in contemporary Fatawa, rooting through the method of easing in the advisory .opinion, and application to contemporary Fatawa personal status :This study consisted of three sections .First topic: the fact that the facilitation of Islamic law and the fact that the fatwa .The second topic: rooting approach to facilitation in the advisory opinion .The third topic: the impact of the easing in contemporary fatwas personal status :She concluded the study 's recommendations and the results of the most important The easing in the advisory opinion which respet Islamic law be in , moderation between stress and indulgence , and this easing has elements of proving a sense of reality and existence , in specific areas , and has reasons reached out to him , and must be easing is set controls legitimacy , and that this easing an impact on contemporary Fatawa
مذكرة ماستر
Keywords: الفتاوى المعاصرة/أثر التیسیر/الأحوال الشخصیة; Contemporary Fatwas/The Effect of Facilitation/Personal Status